Understanding the Complexities of Contemporary Sunni-Shia Relations and Their Prospects Post-Beijing Reconciliation 2023 - astanto, ahmad indri; Nurwahidin, Nurwahidin (Publik : (Jurnal Ilmu Administrasi), 2024)
The relationship between Sunni and Shia communities in the Islamic world has long been a global concern due to its historical, cultural, and political complexities. The purpose of this study is to classify the complexity of contemporary relations between Sunnis and Shias. Furthermore, this study is expected to describe the prospects for Sunni-Shia relations after the Beijing reconciliation agreement. The content analysis research method was chosen based on the instrument used by the researcher, namely the literature on Sunni and Shia developments. The results show that Sunnis, who mostly live in Saudi Arabia, and Shias, who mostly live in Iran, have different perspectives on religious understanding, especially regarding life principles. Shias are known as fanatical worshipers of Muhammad's grandson (Husain) and believe that only his descendants are worthy of becoming the next caliph. Meanwhile, Sunnis believe that the caliph can be chosen through consensus. This difference has become a conflict over the years and has developed into a conflict between Saudi Arabia and Iran. Relations between the two can be strengthened in the Middle East if the Beijing reconciliation agreement is implemented and adhered to together for the advancement of the Arabian Peninsula in the eyes of the world.